Analisis Pengaruh Modal Jam Kerja Dan Jenis Barang Dagang Terhadap Pendapatan Pedagang Kaki Lima Di Pasar Moru Kelurahan Moru Kecamatan Alor Barat Dayakabupaten Alor - Langkola, Lodia; Maro, Yustina; Tang, Sefnat Aristarkus; Sabu, Junius Menase Sau (Peneliti.net, 2023)
The income in this study is the total amount of money received by street vendors at Moru Market, Moru Village, Alor Barat Daya District. The purpose of this study was to determine the effect of capital, working hours and types of merchandise on the income of traders at Moru Market, Moru Village, Alor Barat Daya District, Alor Regency. This type of research is a quantitative description. Samples were taken using saturated sample technique. The sample in this study were 45 traders. Data collection tools used are observation, interviews, and literature studies. The data analysis model used to answer the hypothesis is multiple analysis, t test, F test. This research instrument test is used to measure the level of validity, reliability and classic assumptions from the answers to the research questionnaire. By using the tool to calculate SPSS version 22 For Windows. Based on the results of the validity test for each variable with the Pearson correlation value, the results of the validity test for each variable are declared valid. The results of the reliability test for each variable with the Crobatc Alpha value, the results of the reliability test for each variable are declared reliable. Kolmogrov-Smirnov Normality test results with sig. ≥ then the test results are declared normal. The results of the heteroscedasticity test showed that the value of each independent variable meant that this study did not have heteroscedasticity. The results of the multicollinearity test show that the VIF value > tolerance means that multicollinearity does not occur in this study. The results of the linearity test between the dependent variable and the independent variable show that the deviation from linearity value is > 0.05, so there is a relationship between the dependent variable and the independent variable. The analytical method used is multiple linear regression analysis technique. The results with the t test to answer the first, second, and third hypotheses, while multiple linear regression analysis simultaneously used the F test to determine the fourth hypothesis, namely to determine the Effect of Capital, Working Hours and Types of Merchandise on Trader's Income at Moru Market, Alor Barat District Daya Binongko, Alor Regency. Based on the calculation results of multiple linear regression analysis partially and simultaneously, the significance value of the Capital variable is 0.000, Working Hours is 0.000, Merchandise Type is 0.005, and the simultaneous effect of the significance value of the F test is 0.000b, the test results t and the F test is smaller than alpha (0.05), then the hypothesis testing proposed in this study is as follows: There is an influence of business capital, working hours and types of merchandise on the income of traders in Moru Market, Alor Barat Daya District, Alor Regency .